Cosmetic surgery treatment injuries: the New Zealand experience both at home and from cosmetic surgery tourism - Jonathan Wheeler (Australasian Journal of Plastic Surgery, 2020)
**Objective**: Complications arising from cosmetic surgery are burdensome for the patient and for the community. This article attempts to understand the number of complications arising in patients returning to New Zealand from cosmetic surgery tourism destinations with reference to the number of patients with complications from cosmetic surgery undertaken in New Zealand.